Baldrige aWard winning quality -- 18th edition how to interpret the baldrige criteria for performance excellence - Brown, Mark Graham (Productivity Press, an imprint of Taylor and Francis, 2013)
The Malcolm Baldrige National Quality Award is the highest level of national recognition for performance excellence that a U.S. organization can receive. Now in its 18th edition, Baldrige Award Winning Quality is still the most widely used and recognized book on the Malcolm Baldrige National Quality Award. It provides readers with a simple, yet comprehensive resource, for understanding the most current criteria for this prestigious business performance award. The definitive resource for helping companies achieve world-class results, Baldrige Award Winning Quality? 18th Edition: How to Interpret the Baldrige Criteria for Performance Excellence is the only book on the Baldrige criteria to detail, in simple and straightforward language, every category, examination item, and area to address. From understanding the scoring system to preparing for a site visit, it guides you through all stages in the process. Reflecting the new criteria (2013-2014) that address education and healthcare, this edition outlines a comprehensive plan that is suitable for any company in any industry. Offering detailed explanations of each of the 17 "Examination Items" and the 36 "Areas to Address" that compose the seven major categories, the book reveals exactly what examiners look for in each area and suggests what you need to include. It also discusses